Correction: Disparities in the Burden of HIV/AIDS in Canada. - Robert S Hogg; Katherine Heath; Viviane D Lima; Bohdan Nosyk; Steve Kanters; Evan Wood; Thomas Kerr; Julio S G Montaner (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0047260.].